Ghrelin improves burn-induced multiple organ injury by depressing neutrophil infiltration and the release of pro-inflammatory cytokines - YEGEN, BERRAK; ERZİK, CAN; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (ELSEVIER SCIENCE INC, 2008)
Mechanisms of burn-induced skin and remote organ injury involve oxidant generation and the release of pro-inflammatory cytokines. In this study the possible antioxidant and anti-inflammatory effects of ghrelin were evaluated in a rat model of thermal trauma. Wistar albino rats were exposed to 90 degrees C bath for 10 s to induce thermal trauma. Ghrelin, was administered subcutaneously (10 ng/kg/day) after the burn injury and repeated twice daily. Rats were decapitated at 6 h and 48 h after burn injury and blood was collected for the analysis of pro-inflammatory cytokines (TNF-alpha and IL-1 beta), lactate dehydrogenase (LDH) activity and antioxidant capacity (AOC). In skin, lung and stomach tissue samples malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) and Na+-K+-ATPase activity were measured in addition to the histological analysis. DNA fragmentation ratio in the gastric mucosa was also evaluated. Burn injury caused significant increase in both cytokine levels, and LDH activity, while plasma ACC was found to be depleted after thermal trauma. On the other hand, in tissue samples the raised MDA levels, MPO activity and reduced GSH levels, Na+-K+-ATPase activity due to burn injury were found at control levels in ghrelin-treated groups, while DNA fragmentation in the gastric tissue was also reduced. According to the findings of the present study, ghrelin possesses a neutrophil-dependent anti-inflammatory effect that prevents burn-induced damage in skin and remote organs and protects against oxidative organ damage. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: thermal trauma; ghrelin; cytokine; lipid peroxidation; myeloperoxidase; LIPID-PEROXIDATION; ACYLATED PEPTIDE; THERMAL-INJURY; RATS; ACTIVATION; APOPTOSIS; GLUTATHIONE; MECHANISMS; EXPRESSION; ETHANOL